CBCT Evaluation of Buccolingual Orientation of Inferior Alveolar Canal in Mandibular Posterior Region for Implant Planning - Michelle Kher Wei Chua; Wen Jiong Koh; Smita Nimbalkar; Pravinkumar G. Patil (Hindawi Limited, 2022)
Purpose. Inferior alveolar nerve (IAN) can be subjected to iatrogenic injury during implant surgical procedures. The purpose of this retrospective study was to identify the buccolingual orientation of IAN in posterior mandible as adjunct information for implant planning and to estimate ethnicity-, sex-, and side-related variations in Malaysian population. Material and Methods. A total of 121 CBCT images were viewed with eXamVision software. The buccolingual position of IAN was identified in the posterior region. Buccal bone width (B), canal thickness (C), and lingual bone width (L) were measured at the horizontal canal levels. Kruskal-Wallis H test and Friedman test were used to analyze the buccolingual position. One-way ANOVA was performed to evaluate the variations in B, C, and L values. Results. Overall, most of the IANs were located on the lingual sides of the second molar regions (left: 71.9%; right: 71.1%) and at the centers of the first molar regions (left: 57.9%; right: 47.10%) and exited through the mental foramen before the second premolar regions. There was statistically significant difference in the buccolingual position of the IAN between the sexes in the left second premolar regions (P=0.03). There was variation in B between the sexes in the left first molar regions (P=0.01). Statistically significant differences in C and L were also found between different ethnic groups (P=0.04). Between both sides, there were variations in C in the first molar regions (P<0.001) and the second molar regions (P=0.03). Conclusion. From the second molar to the second premolar, the buccal bone width decreased while the lingual bone width increased. There were variations between ethnicities, sexes, and sides among Malaysians.